PENGARUH MOTIVASI DAN MINAT TERHADAP KEBERHASILAN USAHA MELALUI KEMAMPUAN BERWIRAUSAHA PADA MAHASISWA PESERTA WMK UNIVERSITAS PADJADJARAN - Husein Faryuki Sukarno; Mas Rasmini (JURNAL LENTERA BISNIS, 2024)
The main challenges in the growth of entrepreneurship in Indonesia lie in the low motivation and interest of the community, stemming from uncertainty about business success, lack of access to resources, and reluctance to take potentially inhibiting risks in the entrepreneurial ecosystem. Limited capabilities and knowledge in entrepreneurship also pose significant barriers to the growth of the number of entrepreneurs in Indonesia. Some individuals may lack sufficient knowledge about practical steps to start and run businesses, such as business planning, financial management, or marketing strategies. This research focuses on measuring the influence of interest and motivation on business success through entrepreneurial capabilities. The method employed in this research is quantitative, utilizing data collection techniques involving questionnaires and interviews. The data analysis technique used is square equation modeling (SEM). The study concludes that motivation and interest significantly impact business success, with entrepreneurial capabilities serving as a mediating variable. Key words: Motivation, Interest, Entrepreneurial Capabilities, Sustainability